PENGATURAN RESTRUKTURISASI PEMBIAYAAN DI BANK SYARIAH INDONESIA SELAMA MASA PANDEMI COVID-19 - Mega Ayu Putri Lestari; Dinda Keumala (Reformasi Hukum Trisakti, 2021)
During the Covid-19 pandemic, one of the reliefs provided by the Government was restructuring. The restructuring instruction is regulated in the Financial Services Authority Regulation No. 11/POJK.03/2020 concerning National Economic Stimulus as Countercyclical Impact of the Spread of Coronavirus Disease 2019 as amended by POJK No. 48/POJK.03/2020 and last amended by POJK No. 17/POJK.03/2021. In this case, the Financial Services Authority Regulation is still very general in nature so that the Financial Services Authority instructs the bank to include several provisions in the Bank's Internal Guidelines. The formulation of the problem is how the suitability of restructuring arrangements and differences in restructuring arrangements based on the Financial Services Authority Regulation on National Economic Stimulus as Countercyclical Impact of the Spread of Coronavirus Disease 2019 with restructuring based on Bank Syariah Indonesia Internal Regulations. The research method is normative, descriptive in nature, secondary data supplemented by interviews, qualitative data analysis, and deductive logic. The results of the research, discussion and conclusions; Bank Syariah Indonesia's Internal regulations are in accordance with the Financial Services Authority Regulations with some additional special provisions that are generally regulated in the Financial Services Authority Regulations prevent massive customer defaults at the end the restructuring.